The usage of organizational culture principles in the system to form rail transport specialists (Transport systems and technologies, 2019)
The relevance of the introduction of the railway transport of Ukraine to the necessity of a systematic approach to the concept of corporate culture is determined. Railway transport of Ukraine is the largest corporation in Ukraine, which has a 150-year history and a bright organizational (corporate) culture.Reforming the industry is difficult for a process to perceive, which is not painless. The article describes the problems of the perception of innovation processes by the personnel of the railway transport of Ukraine, which accompanies the reform of PJSC "Ukrzaliznytsia". The list of factors hindering the innovative development of railway transport of Ukraine is given. It is stressed that the main factors hindering innovation processes are organizational and managerial and socio-psychological constraints, which are often the cause of innovative conflicts. The human factor significantly influences the success of innovation processes and the speed of reforms.The necessity and priority of the development of a special strategy and tactics of taking into account the importance of personnel in the issues of reform are substantiated. The introduction of a systematic approach to organizational culture will allow the team to create a healthy psychological climate that will contribute to the overall goal of reforming the railway industry over a short period of time.It is determined that effective personnel management is possible due to the application of principles of organizational culture, the strategy of which is based on the management of PJSC "Ukrzaliznytsya", as well as on university professors of specialized universities that will allow future specialists to adapt more quickly in the conditions of production.
Keywords: corporate culture, innovative process, reformations of railway transport of Ukraine,